1988
DOI: 10.1002/jctb.280430106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interphase mixing on a water–organic solvent two‐liquid phase microbial system: ethanol fermentation

Abstract: Ethanol fermentation bywere correlated with 'log P' values of the solvents. Full activity was observed at log P > 5 and almost none at log P < 4 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…In the emulsion system, the hydrolytic reaction did not significantly proceed because of the strong inhibitory action of ester 1. It was assumed that the interfacial denaturation of lipase and/or the phase toxicity of 1 toward fungal cells appeared in the emulsion system [35,36]. In the two-liquid-phase system, the hydrolysis of ester 1 smoothly proceeded to afford 40 mg ml À1 of alcohol 2 for 8 days since n-decane might be play as a reservoir for 1 and/or 2.…”
Section: Discussionmentioning
confidence: 99%
“…In the emulsion system, the hydrolytic reaction did not significantly proceed because of the strong inhibitory action of ester 1. It was assumed that the interfacial denaturation of lipase and/or the phase toxicity of 1 toward fungal cells appeared in the emulsion system [35,36]. In the two-liquid-phase system, the hydrolysis of ester 1 smoothly proceeded to afford 40 mg ml À1 of alcohol 2 for 8 days since n-decane might be play as a reservoir for 1 and/or 2.…”
Section: Discussionmentioning
confidence: 99%
“…The fermentation process consists of the conversion of glucose obtained from hydrolysis to bioethanol by microorganism media such as yeast, bacteria, and fungi [62,72,73]. Saccharomyces cerevisiae was used for fermentation assays [74][75][76].…”
Section: Fermentationmentioning
confidence: 99%
“…Thus, although it was confirmed that the immobilized fungal spores could stably catalyze the reduction of benzil, which required a coenzyme in a harmless organic solvent, di-n-hexyl ether, the reduction activity of the immobilized spores gradually decreased in the more hydrophilic and toxic solvent, tert-butyl acetate. tert-Butyl acetate maybe extract water molecules from the alginate gel and spores and exhibits molecular toxicity, which is defined as microbial toxicity, due to the hydrophilic molecules dissolved in an aqueous phase 30,31 .…”
Section: A Novel Non-aqueous Bioconversion System Withmentioning
confidence: 99%